2021
DOI: 10.3389/fpls.2021.635327
|View full text |Cite
|
Sign up to set email alerts
|

The Adjustment of Membrane Lipid Metabolism Pathways in Maize Roots Under Saline–Alkaline Stress

Abstract: Plants are frequently confronted by diverse environmental stress, and the membrane lipids remodeling and signaling are essential for modulating the stress responses. Saline–alkaline stress is a major osmotic stress affecting the growth and development of crops. In this study, an integrated transcriptomic and lipidomic analysis was performed, and the metabolic changes of membrane lipid metabolism in maize (Zea mays) roots under saline–alkaline stress were investigated. The results revealed that phospholipids we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…Besides amino acids and sugars, lipids are also important primary metabolites in plants functioning importantly in energy conversion, signal transduction, and stress response processes (Suh et al, 2015 ). Active changes to membrane lipids in plant roots have been observed under many types of abiotic stress conditions, including temperature stress (Zhao et al, 2021 ), salt stress (Xu et al, 2021 ), and nutritional stress (Nakamura, 2013 ). In legumes, lipid metabolism in the root is crucial for nodule formation and development (Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides amino acids and sugars, lipids are also important primary metabolites in plants functioning importantly in energy conversion, signal transduction, and stress response processes (Suh et al, 2015 ). Active changes to membrane lipids in plant roots have been observed under many types of abiotic stress conditions, including temperature stress (Zhao et al, 2021 ), salt stress (Xu et al, 2021 ), and nutritional stress (Nakamura, 2013 ). In legumes, lipid metabolism in the root is crucial for nodule formation and development (Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…6B). In maize, changes in glycophospholipids synthesis pathway’s genes expression were correlated with altered lipids composition after saline treatment 49 , and also lipodome alterations are expected in adapted BY-2.…”
Section: Resultsmentioning
confidence: 93%
“…Salt–alkaline stress is an important and common abiotic stress that can cause water stress, ion toxicity, and even plant death [ 39 , 40 ]. Deepanjali Verma et al found that salt stress can activate MYC2 s through the mitogen activated protein kinase (MAPK) cascade pathway and that MYC2 s regulate the synthesis of Pro by regulating P5CS1 expression [ 41 ].…”
Section: Discussionmentioning
confidence: 99%